Development of Micro, Small Enterprises and Rural Finance in Sub-Saharan Africa : The World Bank's Strategy - Riley, Thyra A.; Steel, William F. (World Bank, Washington, DC, 2012)
African governments place high priority on developing their indigenous private sector to participate in and lead future growth. This goal is constrained, in part, by the absence of a diversified financial sector capable of meeting the full range of the private sector's legitimate demand for financial services, especially among small and informal businesses. A related and equally pressing issue is the ability of the self-employed and rural poor to sustain the economic activities essential to their survival. Internationally, a variety of financial institutions have found ways to make lending to the poor sustainable and profitable and to take advantage of the lesson that even the poor self-employed repay their loans and seek savings opportunities. The challenge in Africa is to build capacity in the financial sector drawing on the lessons learned from international best-practice institutions. This strategy is an integral part of the Africa Region Finance Strategy. The principal pillars of the Finance Strategy are an initial focus on achieving a healthy fundamental policy and regulatory environment and concentration on building sound institutions through human resource and systems development. These themes are reflected in this strategy statement, whose chief objective is to support deepening and diversification of financial markets to serve the broad spectrum of entrepreneurs found in African countries, including the self-employed poor.